Mapping (post)colonial Paris by ear - Waltham-Smith, Naomi 1983- (Cambridge University Press, 2023)
This text refines and extends analyses France's colonial history up to contemporary antiracist and environmental struggles. It narrates the perspective of the urban field recordist, reinventing the bourgeois figure of the flńeur as a feminist-decolonial activist and configuring listening as an expressly spatial practice of mapping the city
Also issued in print: 2023. - Includes bibliographical references
Keywords: Geschichte 2000-2022; Postcolonialism and music / France / Paris; Paris (France) / Intellectual life; Decolonization / France / Paris; Aural history / France / Paris; Music / France / Paris / History and criticism; Flaneur; Sound; Soziale Bewegung; Stadtforschung; Musikleben; Postkolonialismus; Paris